Association of glucokinase, glucokinase regulator, glucose-6-phosphatase catalytic subunit 2 and melatonin receptor 1b genes polymorphisms with type 2 diabetic subjects - Ansari, Neda (2020)
Type 2 Diabetes Mellitus (T2DM) is a complex metabolic disorder characterised by impaired insulin secretion, insulin resistance, and hyperglycemia, caused by the defects in pancreatic b-cells. Although evidence suggests that multiple genetic and environmental factors are involved in the development and progression of T2DM, Still the underlying causes are unknown and have not been fully elucidated. There have been a variety of genetic studies concerning Type 2 Diabetes Mellitus, and some of them showed an association with the occurrence of T2DM. Although there are various candidate genes have been associated with the T2DM in various populations with conflicting results, variations found in Glucokinase (GCK), glucokinase regulatory protein (GCKR), Glucose-6-phosphatase 2(G6PC2) and Melatonin receptor type 1B (MTNR1B) genes are not well studied particularly among Asians. Glucokinase is the key glucose phosphorylation enzyme that regulates glucose-stimulated insulin secretion from pancreatic beta cells and glucose metabolism. A few selected genes polymorphism variant shown to be associated with increased risk of TDM, hyperglycaemia and impaired beta-cell function. The main objective of this study was to determine the candidate genes polymorphism involved in essential Type 2 Diabetes Mellitus among Malay subjects. Since, there have been a variety of genetic association studies of, GCK, GCKR, G6PC2 and MTNR1B conducted on a different population; however, no study was done on Malaysia populations and consistent with Type2DiabetesMellitus.Genetic polymorphism is serving as molecular biomarkers for the detection of the individual at risk of developing the disease. This association study included 200 of subjects without Diabetes as control and 200 of subjects with Diabetes type 2 as a case. Extraction genomic DNA was done all subjects. GCK gene polymorphism was detected using Polymerase Chain reaction (PCR) followed by Restriction Fragment Length Polymorphism (PCR-RFLP). The PCR products were digested with MwoI (Fermentas) restriction enzyme at 60°c for 20 min. The RFLP products were detected using 2% agarose gel electrophoresis. GCKR, G6PC2, and MTNR1B gene were detected by real-time PCR (RT-qPCR) with Taq-Man probes. Genotype and allele frequencies in case and control samples were compared by using Chi-Square test while characteristic clinical parameters and social-demographic background were analysed using descriptive statics. In this study also the findings have shown that family history of T2DM is high among the subjects (71.3%) compared to the control subjects (54.1%) highlighting the importance of family history assessment in prevention and screening programs and simple measurement of diabetes risk. Body mass index (BMI), fasting blood glucose (FPG), HbA1c, systolic blood pressure (SBP), diastolic blood pressure (DBP) and cholesterol is highly significant (p<0.05) between T2DM and control subjects recognizing the risk factors of T2DM among Malay ethnics in Malaysia. However, the other risk factors such as smoking, waist-hip ratio (WHR), high-density lipoprotein (HDL) and triglycerides (TG) did not reveal any significant difference between cases and controls (p > 0.05). The results of this study were show that the genotypes and allele frequencies of GCK rs1799884 A/G, GCKR rs780094 T/C, and MTNR1B rs10830963 C/G gene were highly significant risk of developing T2DM Diabetes amongst Malays subjects as compared to the healthy (p<0.05), whereas there appears to be no significant association between the genetic polymorphism of G6PC2 rs560887 A/G gene. Hence, this candidate genes as possible genetic biomarker and risk factor for Diabetes Type 2 as a case in Malay subjects.